1988
DOI: 10.1063/1.100178
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of photoluminescence measurements with the composition and electronic properties of chemically etched CdTe surfaces

Abstract: We have performed photoluminescence (PL) measurements on chemically etched single-crystal p-CdTe. In addition, x-ray photoemission measurements have been used as a guide to surface stoichiometry for each chemical treatment. The relative intensities of the 0.875±0.005 eV and 1.125±0.005 eV PL bands are seen to be linked to the preferential depletion of either Cd or Te from the CdTe surface. Furthermore, the energies of these deep level transitions measured at T=4 K show remarkable agreement with the two values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 12 publications
0
29
0
Order By: Relevance
“…It is also worth re-visiting the PL measurements carried out on bulk CdTe wafers purchased from Eagle Pitcher, in the past by the main author [10]. Figure 10 shows the PL spectra obtained at 4 K, together with corresponding X-ray photo-electron spectra (XPS) of the surfaces investigated.…”
Section: Bulk Cdte From Eagle Pitchermentioning
confidence: 99%
“…It is also worth re-visiting the PL measurements carried out on bulk CdTe wafers purchased from Eagle Pitcher, in the past by the main author [10]. Figure 10 shows the PL spectra obtained at 4 K, together with corresponding X-ray photo-electron spectra (XPS) of the surfaces investigated.…”
Section: Bulk Cdte From Eagle Pitchermentioning
confidence: 99%
“…7 Schematic diagrams summarising CdTe grain growth patterns, corresponding XRD spectra and approximate solar cell efficiencies against growth or heat treatment temperature. Note the three regions identified with a sudden phase transition at ST1 = 385 °C, and a slow phase transition taking place after ST2 >430 °C [35] in a comprehensive research programme [3,56,58,59] and a peculiar effect based on fermi level (FL) pinning at n-CdTe/metal interfaces was observed. This work confirmed Schottky barrier formation at the above interface is heavily dependent on Fermi level pinning at one of the five experimentally observed defect levels E1, E2,… E5 (see Fig.…”
Section: Cds/cdte Device Issuesmentioning
confidence: 99%
“…8b). Furthermore, it was found that E1, E2 and E3 dominate when the CdTe surface is rich in Te, and E4 and E5 dominate when the CdTe surface is rich in Cd [56,58]. Therefore, in order to form large Schottky barriers, Fermi level should be pinned at E5, closer to the valence band maximum.…”
Section: Cds/cdte Device Issuesmentioning
confidence: 99%
See 2 more Smart Citations